Sex in the cold: taxonomic reorganization of psychrotolerant yeasts in the order Leucosporidiales - de Garcia, Virginia (2015)
Species of Leucosporidiales are a group of psychrotolerant yeasts with biotechnological potential. In the present work,we studied the phenotypic, genetic and sexual characteristics of three species of this genus (Leucosporidium scottii,Leucosporidiella creatinivora and Le. yakutica) to clarify the evolutionary relationship among these closely related taxa. Fromthe results obtained, it becomes clear that these yeasts can interbreed. Although genetic delimitation is possible for thethree species, the extent of nucleotide substitutions and phenotypic differences observed between them are lower thanthat expected for species that have ended the speciation process. Our taxonomic conclusion is to maintain the three taxauntil further genomic data are gathered. However, the concept of L. scottii species complex is proposed for this group ofspecies. Finally, we transfer all Leucosporidiella and Mastigobasidium species to Leucosporidium (Leucosporidiales), and, inorder to end the polyphyly condition of these taxa, we propose the new genus Pseudoleucosporidium gen. nov. and the newcombination Peudoleucosporidium fasciculatum comb. nov.